2020
DOI: 10.30684/etj.v38i7a.546
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Cost-Influencing Factors Potentially Controllable by Main Contractors in Construction Projects in Iraq

Abstract: Cost overrun in construction projects is a common phenomenon in Iraq. This might occur due to diversity of factors. This study aims to identify the factors influencing construction projects cost that are potentially controllable by main contractors. A field study through a questionnaire survey was directed to a sample of related Iraqi professional engineers from general contracting companies at both public and private sectors. Their opinions on the impact and frequency of each factor were investigated. The que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…With maximum profit in mind, the contractor will have to turn to cost monitoring and control for assistance. Construction firms need to continuously improve their efficiency in cost control [30].…”
Section: Figure 3: Cost Control Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…With maximum profit in mind, the contractor will have to turn to cost monitoring and control for assistance. Construction firms need to continuously improve their efficiency in cost control [30].…”
Section: Figure 3: Cost Control Modelmentioning
confidence: 99%
“…According to [33], project cost reports to be used for cost monitoring and control in the construction firms were investigated as shown in Figure 10. According to [34], Microsoft Excel is an important tool for control. Also, some methods of cost control were identified as the following:…”
Section: Figure 3: Cost Control Modelmentioning
confidence: 99%
“…Authors in [1] concluded that cost deviation is caused by insufficient information, poor planning, unclear employer requirements, and change in orders during the implementation phase. Authors in [4] mentioned that the use of modern technologies and tools, the use of modern design programs, the establishment of solid rules, and the use of work-study techniques are factors that contracting companies should focus on. Authors in [5] found that the factors that influence cost are delays in payments from the client, the maturity period of the down payment, payment terms, down payment, project delay, poor planning, changes in orders, and inaccurate project duration.…”
Section: Introductionmentioning
confidence: 99%